Structural Basis for Broad Neutralization of Hepatitis C Virus Quasispecies - Lapierre, Pascal (Public Library of Science, 2011)
Monoclonal antibodies directed against hepatitis C virus (HCV) E2 protein can neutralize cell-cultured HCV and pseudoparticles expressing envelopes derived from multiple HCV subtypes. For example, based on antibody blocking experiments and alanine scanning mutagenesis, it was proposed that the AR3B monoclonal antibody recognized a discontinuous conformational epitope comprised of amino acid residues 396–424, 436–447, and 523–540 of HCV E2 envelope protein. Intriguingly, one of these segments (436–447) overlapped with hypervariable region 3 (HVR3), a domain that exhibited significant intrahost and interhost genetic diversity. To reconcile these observations, amino-acid sequence variability was examined and homology-based structural modelling of E2 based on tick-borne encephalitis virus (TBEV) E protein was performed based on 413 HCV sequences derived from 18 subjects with chronic hepatitis C. Here we report that despite a high degree of amino-acid sequence variability, the three-dimensional structure of E2 is remarkably conserved, suggesting broad recognition of structural determinants rather than specific residues. Regions 396–424 and 523–540 were largely exposed and in close spatial proximity at the surface of E2. In contrast, region 436–447, which overlaps with HVR3, was >35 Å away, and estimates of buried surface were inconsistent with HVR3 being part of the AR3B binding interface. High-throughput structural analysis of HCV quasispecies could facilitate the development of novel vaccines that target conserved structural features of HCV envelope and elicit neutralizing antibody responses that are less vulnerable to viral escape.